2022
DOI: 10.1057/s41307-022-00269-x
|View full text |Cite
|
Sign up to set email alerts
|

Information Needs in Higher Education Institutions: Stock Valuation or Decision-Making?

Abstract: Numerous higher education institutions apply a full costing system in their accountingmodel due to the imposition of formal agents (governments/funding institutions), or bysuggestion of informal agents (associations). This paper analyzes whether therationale applied by these agents to justify the use of the full costing rather than thedirect/variable system is consistent with the theoretical bases underlying both costingsystems. Methodologically, we review the mainstream literature that explores the linksbetwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Studies (Sanches et al 2022) have suggested that the failure of ABC implementation is often because of contextual factors such as organisational values, culture and climate, rather than the process of implementation itself. Activity-based costing aims to reduce distortions caused by arbitrary allocation of indirect costs in traditional systems.…”
Section: Environmental or Contextual Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies (Sanches et al 2022) have suggested that the failure of ABC implementation is often because of contextual factors such as organisational values, culture and climate, rather than the process of implementation itself. Activity-based costing aims to reduce distortions caused by arbitrary allocation of indirect costs in traditional systems.…”
Section: Environmental or Contextual Factorsmentioning
confidence: 99%
“…Support costs, such as information technology (IT), financial aid, library, security, admissions, examinations and student services, that were previously considered as fixed and irrelevant in decision-making have become increasingly important areas of resource consumption. Traditional costing systems often distort costs and do not reflect the increasing complexities, advanced technology and multiplicity of programmes and services that are now offered by universities (Sanches, Souto & Gago-Rodríguez 2022). These changes demand more accurate cost allocation techniques.…”
Section: Introductionmentioning
confidence: 99%